2016
DOI: 10.1111/aji.12475
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Inflammation: Association between Leukocyte Concentration and Levels of Immune Mediators

Abstract: EMMPRIN, MMP-8, HA, β-defensin, and NGAL are elevated in women with vaginal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…The intra-amniotic inflammatory process associated with elevated amniotic fluid concentrations of HBD-1 may be mediated by toll-like receptors (TLRs) such as TLR-4 and TLR-2, which had been implicated in the mechanisms that lead to secretion of defensins by epithelial cells 169 . Our data, along with previous studies demonstrating that MIAC results in an increased amniotic fluid concentration of lactoferrin 81, 82 , lysozyme 19, 21 , and bacterial/permeability-increasing protein 20 among others 107, 170172 , suggest that antimicrobial peptides participate in the soluble host defense mechanisms against intra-amniotic infection 173, 174 in women who underwent spontaneous preterm labor and delivered preterm.…”
Section: Discussionsupporting
confidence: 81%
“…The intra-amniotic inflammatory process associated with elevated amniotic fluid concentrations of HBD-1 may be mediated by toll-like receptors (TLRs) such as TLR-4 and TLR-2, which had been implicated in the mechanisms that lead to secretion of defensins by epithelial cells 169 . Our data, along with previous studies demonstrating that MIAC results in an increased amniotic fluid concentration of lactoferrin 81, 82 , lysozyme 19, 21 , and bacterial/permeability-increasing protein 20 among others 107, 170172 , suggest that antimicrobial peptides participate in the soluble host defense mechanisms against intra-amniotic infection 173, 174 in women who underwent spontaneous preterm labor and delivered preterm.…”
Section: Discussionsupporting
confidence: 81%
“…This may result in an overgrowth of anaerobic or facultative Gram-negative bacteria, which are usually associated with bacterial vaginosis [ 231 ]. The report of Beghini also found that the concentrations of NGAL in the vaginal fluid were higher in women with vaginal inflammation [ 232 ].…”
Section: Ngal In Biological Fluids and Additional Functions Of Ngalmentioning
confidence: 99%
“…The presence of neutrophil peptides 1–3 (defensins) is closely correlated with the presence of vaginal WBCs [ 16 ]. A recent study demonstrated that proinflammatory cytokines EMMPRIN, MMP-8, and NGAL levels were significantly associated with PMNLs count in vaginal Gram stain samples where the vaginal inflammation was defined as >4 PMNLs /HPF [ 17 ]. The number of PMNLs in cervix has been observed to be stable throughout the menstrual cycle [ 1 , 18 ], but sperms influence the cervical inflammatory response and PMNLs increase sharply in cervix after insemination, caused by increased local production of IL-8 in response to seminal plasma [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%